2020
DOI: 10.1371/journal.ppat.1009020
|View full text |Cite
|
Sign up to set email alerts
|

Brucella suppress STING expression via miR-24 to enhance infection

Abstract: Brucellosis, caused by a number of Brucella species, remains the most prevalent zoonotic disease worldwide. Brucella establish chronic infections within host macrophages despite triggering cytosolic innate immune sensors, including Stimulator of Interferon Genes (STING), which potentially limit infection. In this study, STING was required for control of chronic Brucella infection in vivo. However, early during infection, Brucella down-regulated STING mRNA and protein. Down-regulation occurred post-transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Many studies have shown Brucella subversion of TLR signaling through proteins such as Tcbp, which leads to decreased proinflammatory cytokine expression [10]. Additionally, Brucella microRNAs can lead to the downregulation of the mRNA and protein expression of innate immune PRRs [34]. These mechanisms likely did not occur in our gDNA studies as there was no inclusion of these immunosuppressive proteins or production of inhibitory microRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have shown Brucella subversion of TLR signaling through proteins such as Tcbp, which leads to decreased proinflammatory cytokine expression [10]. Additionally, Brucella microRNAs can lead to the downregulation of the mRNA and protein expression of innate immune PRRs [34]. These mechanisms likely did not occur in our gDNA studies as there was no inclusion of these immunosuppressive proteins or production of inhibitory microRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…Huang et al reported miR-24 binding to rat STING mRNA [ 30 ]. Recently Shen et al and Khan et al have also reported this targeting in a liver ischemia model and Brucella infection respectively [ 31 , 32 ]. As anticipated, transfection of synthetic miR-24 caused a reduction of STING protein expression ( Fig 1C ); conversely, transfection of antimiR-24 enhanced STING expression ( Fig 1D ).…”
Section: Resultsmentioning
confidence: 99%
“…with 1 × 10 6 CFU B. abortus strain S2308 and sacrificed at 1, 2 or 3 weeks post infection. To measure Brucella CFU, the spleens extracted from the animals were macerated in 10 ml of sterile saline solution (NaCl 0.9%) using a steel sieve and plated on Brucella broth agar and after 3 days, the number of CFU was counted as described previously (Khan et al, 2020). To measure intracellular multiplication in macrophages, macrophages were plated onto 24‐well plates at the density of 5 × 10 5 cells per well.…”
Section: Methodsmentioning
confidence: 99%